A reproducibility study on invasion in small pulmonary adenocarcinoma according to the WHO and a modified classification, supported by biomarkers - Thunnissen, Erik; Blaauwgeers, Hans; Filipello, Federica; Lissenberg-Witte, Birgit; Minami, Yuko; Noguchi, Masayuki; Quesne, John Le; Papotti, Mauro Giulio; Flieder, Douglas B.; Pelosi, Giuseppe; Sansano, Irene; Berezowska, Sabina; et al. (Lung cancer, 2024)
Objectives - Evaluating invasion in non-mucinous adenocarcinoma (NMA) of the lung is crucial for accurate pT-staging. This study compares the World Health Organization (WHO) with a recently modified NMA classification. - Materials and Methods - A retrospective case-control study was conducted on small NMA pT1N0M0 cases with a 5-year follow-up. Seventy cases were reviewed by 42 pulmonary pathologists first according to the WHO classification and after tutorial according to a modified classification. A third round was conducted based on feedback from 41 peers of previous rounds. Additionally, orthogonal biomarker analysis was performed. - Results - In the first two rounds, 42 pathologists from 13 countries assessed all 70 cases, while 36 pathologists evaluated 41 non-unanimous cases in the third round. Kappa values for invasiveness increased in rounds 1, 2, and 3 to 0.27, 0.45 and 0.62, respectively. In contrast to low variation in total tumor size measurements (6 %), a marked increase in invasive tumor size variation was observed (42 %), which was associated with high uncertainty. In the third round 10 cases were non-invasive, all without recurrence. The modified classification showed in the 3rd round marked reduction of the variation in pT staging compared to the current WHO classification. Proliferation rate, tumor mutational burden, and transcriptomic profiles supported the distinction between invasive cases and non-invasive cases of the modified classification. - Conclusion - The modified classification demonstrates essentially higher reproducibility compared to the current WHO classification in NMA. The modified classification proves valuable in identifying low-risk lesions that are entirely non-invasive, and is supported by biomarker analysis.
Gesehen am 14.07.2025